Basalt fibrous fiber concrete and his properties learning - Xolmirzaev Sattar Abdujabbarovich,; G‘ulаmiddinov Sarvarjon G‘ayratjonnovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Requirements for the efficiency and quality of construction work will be set for the development of production of fiber concrete and waste-based concrete products. In order to do this properly, it is necessary to reduce the total energy consumption of materials and structures, production development, materials, construction cost and labor, reducing the weight of buildings and structures, repair and their construction and operation.